GAMIFICATION AS A SERVICE BERBASIS PHP - Akhmad Budi (Jurnal Informatika dan Bisnis, 2021)
This research is caused by the problem of an absence of a service about improving motivation and achievement in working environment at Koding Next Company. The author applies the concept of gamification on this service. The conceptualization of gamification in this service uses 9 elements of motivational affordance, which are point, leaderboard, badges, clear goals, feedback, reward, progress, and challenge. The motivational affordance affects the psychological outcomes and behavioral outcomes. The author conducts field studies, interview to the users who will be directly involved with this service, and a literature review of previous researches that share the same topic. Through this research, the author finds out that the concept of gamification can be applied with PHP through API as the service. The data in this service can be accessed by web and other platforms to support the concept of gamification. Through the research process and the making of the service process that has been going on, the author concludes that this service can apply Gamification as a Service at Koding Next Company. This service is capable to improve the motivation and achievement of employees. Kata kunci: gamification, service, gamification as a service, api